ANALISIS SWITCHING INTENTION PENGGUNA JASA LAYANAN RUMAH KOS DI SIWALANKERTO: PERSPEKTIF KUALITAS LAYANAN DAN KEPUASAN PELANGGAN - Liza Agustina Maureen Nelloh; Carolina Chandra Purwanto Liem (Institute of Research and Community Outreach - Petra Christian University, 2011)
The Increasing number of new universities nowadays in Surabaya led to higher competition in services especially in boarding house services. This study wanted to see the switching intention from the point of service quality and customer satisfaction which is a fraction of the integration model of push, pull, and mooring factors in the sector of boarding house users. To test the hypothesis, the researcher use PLS (Partial Least Sqaure). The results of this study indicate that the service quality have a significant and positive impact on customer satisfaction, as well as having a significant negative impact on switching intention. However, customer satisfaction can not have a significant effect on switching intention. Managerial implications of this research would be to improve service quality and lower the user's intention to switch to another houses and it would applied in service boarding house for both Siwalankerto area and as general in Surabaya.